Porophyllum Genus Compounds and Pharmacological Activities: A Review - María José Vázquez-Atanacio; Mirandeli Bautista-Ávila; Claudia Velázquez-González; Araceli Castañeda-Ovando; Manasés González-Cortazar; Carolina Guadalupe Sosa-Gutiérrez; Deyanira Ojeda-Ramírez (MDPI AG, 2021)
The genus Porophyllum (family Asteraceae) is native to the western hemisphere, growing in tropical and subtropical North and South America. Mexico is an important center of diversification of the genus. Plants belong of genus Porophyllum have been used in Mexican traditional medicine to treat kidney and intestinal diseases, parasitic, bacterial, and fungal infections and anti-inflammatory and anti-nociceptive activities. In this sense, several trials have been made on its chemical and in vitro and in vivo pharmacological activities. These studies were carried on the extracts and isolated compounds and support most of their reported uses in folk medicine as antifungal, antileishmanial, anti-inflammatory, anti-nociceptive and burn repair activities, and as a potential source of new class of insecticides. Bio guided phytochemical studies showed the isolation of thiophenes, terpenes and phenolics compounds, which could be responsible for the pharmacological activities. However, more pre-clinical assays that highlight the mechanisms of action of the compounds involved in pharmacological function are lacking. This review discusses the current knowledge of their chemistry, in vitro and in vivo pharmacological activities carried out on the plants belonging to the Porophyllum genus.